Self-Awareness pada Ibu PSK dalam Pendidikan Seksual untuk Anak di Lingkungan Lokalisasi Gedangsewu Kecamatan Pare - Nesti C. Nagari; Pravissi Shanti (Jurnal Penelitian Kualitatif Ilmu Perilaku, 2021)
This study aims to describe the self awareness that exists in sex workers mothers related to the way and awareness of themselves in providing sexual education for their children. This study uses qualitative research methods with a phenomenological research model. Data collection techniques are done by interview and observation. Data analysis techniques using thematic analysis techniques. Checking the validity of the data is done by using interpretive validity by triangulating data. The study was conducted in the Gedangsewu red-light district in Pare with the number of subjects being 3 mothers who work as sex workers with a range of 9- 14 years old children and significant others totaling 3 people. Research shows that two subjects with female children say that providing sexual education for children is important to protect their children from negative environmental influences. While one subject with a male child stated that sexual education was not important given to her child because she considered that it was more important formal education and religious education. The results of the study explain that sex workers have a level of self-awareness capable of realizing the risks of their work, understanding the negative effects of the environment on children, and being able to set good examples to their children. Sexual education provided by mothers to children includes limiting who children associate with, regulating how to dress children, providing reproductive knowledge according to their abilities, and providing rules related to the association of children.